Pathways to Resistance: Theorizing Trauma and Women's Use of Force in Intimate Relationships - Becker, Patricia (Violence against women, 2025)
Using a feminist pathways general strain perspective, we explore the victim–offender continuum for women who perpetrated intimate partner violence/abuse (IPV/A). We use data from 86 women court-mandated to “female offender” domestic violence treatment programs, located in an American East Coast state, who were surveyed about their adverse childhood experiences and mental health/well-being as adults. Findings from bivariate linear regressions indicate childhood trauma negatively affects adult mental health/well-being, exacerbated for Black Indigenous People of Color women, suggesting a victim rather than an offender categorization for women using force against their abusive partner. Results imply the need to consider women's traumatic histories and IPV/A victimization, given an incident-driven system that criminalizes victimization over the life course.